Kontribusi Sektor Pertanian Terhadap Pertumbuhan Ekonomi Di Provinsi Riau - Trian Zulhadi (Jurnal Ekonomi, 2009)
Agricultural sector plays a very important role in economic growth of each country. Even though itscountribution has decreased continously compared with other sectors, but its contribution to labourforce in reducing unemployment is significant. The economic transformation from agriculture sector toindustrial sector is a characteristic of developed country. In this respect, capital and labour, an withrate play pivotal role for agriculture development. Therefore the objective of this paper is to measurethe countribution the agriculture sector towards economic development. Gross Domestic Product(GDP), is used as a proxy of economic growth. All the independent variables in this research areagriculture sector (Gp), industrial sector (Gi), and service sector (Gs), Due to multivariatemulticolinearity amongs independent variable area was removed.The result of OLS regression shows that the elasticity of the agriculture sector contribute for 2.77percent,industrial sector was 3.00, and Service sector was 16.83. This means that an increase theeconomic growth as much as 2.77 per cent, likewise, an increase of one per cent in each of bothindustrial and service sectors would increase the economic growth, as much as 3.00 percent and 16.83percent.